Evaluating salient object detection in natural images with multiple objects having multi‐level saliency. Issue 10 (8th July 2020) - Yildirim, Gökhan; Sen, Debashis; Kankanhalli, Mohan; Süsstrunk, Sabine
Abstract : Salient object detection is evaluated using binary ground truth (GT) with the labels being salient object class and background. In this study, the authors corroborate based on three subjective experiments on a novel image dataset that objects in natural images are inherently perceived to have varying levels of importance. The authors' dataset, named SalMoN (saliency in multi‐object natural images), has 588 images containing multiple objects. The subjective experiments performed record spontaneous attention and perception through eye fixation duration, point clicking and rectangle drawing. As object saliency in a multi‐object image is inherently multi‐level, they propose that salient object detection must be evaluated for the capability to detect all multi‐level salient objects apart from the salient object class detection capability. For this purpose, they generate multi‐level maps as GT corresponding to all the dataset images using the results of the subjective experiments, with the labels being multi‐level salient objects and background. They then propose the use of mean absolute error, Kendall's rank correlation and average area under precision–recall curve to evaluate existing salient object detection methods on their multi‐level saliency GT dataset. Approaches that represent saliency detection on images as local‐global hierarchical processing of a graph perform well in their dataset.